An Electronic Actinometer for measurements in narrow spectral ranges (MAUSAM, 1957)
This paper describes the use of capacitance bolometers for special measurements of the direct solar radiation. Electronic and optical design factors are outlined, followed by constructional and operational details, Indicating methods for capacitance bolometers are discussed with particular reference to this electronic actinometer.